How Young is Your Heart ? - Regmi, Prakash Raj (Nepalese Heart Journal, 2006)
A low calorie, nutritionally balanced diet has been associated with slowing the ageing process of the heart - which is why this year's World Heart Day campaign asks: “How Young is Your Heart?"